PELAYANAN DENGAN KEPUASAN KONSUMEN PADA TOKO OBAT ANDIKA FARMA BENGKULU - Rudi Hartono (Jurnal Adminitrasi Bisnis Nusantara, 2023)
The purpose of this study was to determine the relationship of service with customer satisfaction at the drug store Andika Farma Bengkulu. The method used is the analyst Spearman rank correlation and testing the accuracy of data by t test.  Spearman rank test results of 0.831. This suggests that there is a very strong correlation between customer satisfaction in service with the purchase of medicines in drugstores Andika Farma Bengkulu. With the service is friendly, courteous and quick from the drug store employee Andie Farma Bengkulu, then consumers will feel very happy and satisfied with the service, so that consumers will come again to make purchases of drugs at the drug store Andika Farma Bengkulu. Results of hypothesis testing tcount greater than the value ttable (9.209> 1.686) means that the service has a positive and significant relationship with customer satisfaction at the drug store Andika Farma Bengkulu. It is explained that there is a close relationship between services with customer satisfaction, if the services provided by employees Andika Farma drugstore Bengkulu then the consumer will feel satisfied and happy shopping at drug stores Andika Farma Bengkulu